Personality Traits, Subject Matter, Knowledge, and Teaching Skills of Secondary Teachers - I. Ani, Mercy; O. Obih, Solomon (Polaris Global Journal of Scholarly Research and Trends, 2023)
The study examined the personality trait, subject matter, knowledge of the subject, and teaching skills of secondary school teachers. The major goal of the study was to examine the teaching profession concerning the knowledge of the subject matter, teaching skills, and personality traits of Nigerian secondary school teachers. A survey research design was adopted for the study. The population comprised all the public secondary school teachers in South East Nigeria. A purposive sampling technique was used to draw 150 teachers from the five states. The instrument for data collection was a four-point scale researchers’ developed questionnaire. Two research questions and two null hypotheses guided the study. The research questions were answered using mean and standard deviation while the t-test was used to test the null hypotheses at a 0.05 level of significance. The result of the study showed that teachers have adequate knowledge of their subject matter with teaching skills and personality traits that improve teaching and learning in schools.